2004
DOI: 10.1093/ajcn/80.4.998
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on calcium absorption in postmenopausal women

Abstract: A late age-related decrease in calcium absorption is seen in postmenopausal women in addition to the decline that occurs at menopause. This decrease could be due to a decline in either the active calcium transport or diffusion component of the calcium absorption system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(82 citation statements)
references
References 26 publications
4
75
1
2
Order By: Relevance
“…Under our experimental conditions, the acute calcium uptake from the fresh yoghurt was higher than from the pasteurized, as evidenced by the increase in circulating plasma levels of calcium one hour after intake [31]. The heat treatment of yoghurt to increase the shelf live of the product could diminish the effect on lactose digestibility due apparently to enzymatic inactivation [32], together with the proposed effect on orocaecal transit time, described as shorter for the pasteurized yoghurt [23].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Under our experimental conditions, the acute calcium uptake from the fresh yoghurt was higher than from the pasteurized, as evidenced by the increase in circulating plasma levels of calcium one hour after intake [31]. The heat treatment of yoghurt to increase the shelf live of the product could diminish the effect on lactose digestibility due apparently to enzymatic inactivation [32], together with the proposed effect on orocaecal transit time, described as shorter for the pasteurized yoghurt [23].…”
Section: Discussionmentioning
confidence: 67%
“…However, calcium utilization depends upon individual factors, such as the lactase-deficiency degree as well as on food characteristics [30]. Thus, several studies have shown that yoghurt is better tolerated than milk [11], because some lactase activity from yoghurt bacteria could participate in lactose digestion, as well as the delayed oro-cecal transit time [23,31]. Therefore, yoghurt could allow lactose maldigesting people to comfortably consume a dairy food naturally rich in calcium.…”
Section: Discussionmentioning
confidence: 99%
“…In women, the two major causes of bone loss are estrogens deficiency after the menopause and age related processes [13]. Bone turnover increases to high levels in women soon after menopause [14] in postmenopausal women, estrogen deficiency may induce calcium loss due to decreased intestinal calcium absorption and decreased renal calcium conservation [14][15][16]. So there are more chances of decreased calcium levels in postmenopausal women.…”
Section: Resultsmentioning
confidence: 99%
“…In postmenopausal women, reviews of over 20 studies have concluded that calcium supplementation can decrease bone loss by ≈1% per year [16]. Therefore, calcium supplementation has been shown to be effective in retarding bone loss in postmenopausal women.…”
Section: Resultsmentioning
confidence: 99%
“…This appears to be the result of a developing resistance to the action of 1,25(OH) 2 D; fractional calcium absorption from diets containing different levels of calcium was correlated with serum 1,25(OH) 2 D concentration in young (28.7 ± 5.3 years) but not in older (72.5 ± 3.0 years) women (Pattanaungkul et al, 2000). The menopause is associated with a significant fall in calcium absorption, possibly as a result of lower oestrogen levels affecting receptors in the small intestine (Nordin et al, 2004). Data from early radioisotope studies show a continuous reduction in absorption from the age of 60 years in men and women (Bullamore et al, 1970).…”
Section: Intestinal Absorptionmentioning
confidence: 91%